FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEKURANGAN ENERGI KRONIS (KEK) PADA IBU HAMIL - Amalina, Nurul; Kasoema, Rahmi Sari; Yani, Linda (Universitas Fort de Kock Bukittinggi, 2023)
Across Indonesia's 34 provinces, a total of 283,833 pregnant women with Lila measurements below 23.5 cm (indicating KEK) were identified among 3,249,503 pregnant women. In Jambi Province in 2020, there were 62 reported cases out of 64,365 live births. Among 6,785 pregnant women across 16 community health centers, 317 individuals experienced Chronic Energy Deficiency (KEK). This study aims to discern the factors influencing KEK in pregnant women at Singkut Community Health Center. Employing an analytical survey with a case-control approach, the research was conducted during March-April 2023. The study's population consisted of 646 pregnant women in Singkut Community Health Center's jurisdiction, with a sample size of 90 pregnant women, equally divided between 45 case and 45 control participants. Total sampling was employed as the sample technique. The findings indicated that 50.0% of respondents experienced CED, 52.2% of respondents had limited education, 75.6% were primipara, and 24.4% were multiparous. Furthermore, 51.1% of respondents had suffered from infectious diseases, and 58.9% had low income. Bivariate tests revealed significant associations between education (p-value = 0.000; OR 112.000), parity (p-value = 0.000; OR 38.500), infectious diseases (p-value = 0.000; OR 52.000), income (p-value = 0.000; OR 19,692), and KEK. The study concludes that education, infectious diseases, and income are correlated with KEK, while no relationship was found between parity and KEK among pregnant women in the Singkut Health Center's catchment area. Pregnant women are advised to prioritize education, income, and infectious disease management.Keywords: KEK, Education, Parity, Infectious Diseases, Income